Risk Factors for Domestic Homicide: Immigrant & Canadian-born Populations - Kalaichandran, Sakthi (2018)
Domestic violence is a critical human rights issue that can escalate to cases of domestic homicide. Globally, approximately 30% of women in relationships have reported experiencing violence at the hands of an intimate partner. In Canada this pattern is echoed, as over 25% of police-reported violent offences were from victims of domestic abuse. Recent research has revealed that immigrant & refugee victims experience unique risk factors that may render them more vulnerable to this form of violence. Yet, despite this burgeoning research area, and Canada’s diverse population of 6 million immigrants, there is a dearth of research pertaining to domestic violence risk factors facing immigrant victims in a Canadian context. Indeed, the shifting sociodemographic profile of Canada's population calls for culturally-informed risk assessment, risk management & safety planning tools to protect as many people as possible from domestic violence & homicide. Therefore, this study investigated factors that pertain to a victim’s vulnerability to violence across immigrant and Canadian-born populations. Although several factors, such as actual or pending separation, were shared across both demographics, other factors, such as social isolation, featured more prominently in cases of immigrant domestic homicide victims. By identifying these shared and unique characteristics, front line workers & policy makers will be informed of important trends that can influence the creation of research-based & culturally-relevant risk assessment, risk management and safety planning strategies